PENGARUH FAKTOR SOSIAL EKONOMI DAN DEMOGRAFI TERHADAP TINGKAT FERTILITAS DI DENPASAR BARAT - Pranata, I Gede Arya; Sudibia, . I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Problems faced by almost all developing countries in the world, including Indonesia, the population growth rate (LPP) fluctuates every year. Fertility, mortality, and migration are the components that influence population changes. This study aims to determine the effect of socioeconomic and demographic factors on the level of fertility in West Denpasar. Used primary and secondary data. This research was a total sample of PUS as 123 people with a probability sampling method. Data analysis technique used in path analysis. The results this study indicate that employment status, education level, family income and migration status have a direct positive and significant effect on the duration of contraceptive use in West Denpasar. Level of education has negative not significant effect on the number of children born alive, while the status of work, migration status and duration of use of contraception have a significant and significant effect on the number of children born alive in West Denpasar, length of use of contraception is a variable that can mediate the effect of the variable work status , education level, family income, and migration status of the number of children born alive in West Denpasar. Keywords: fertility, duration of use of contraception, path analysis techniques